2011
DOI: 10.1007/s10549-011-1666-0
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive factors and histologic subtype in relation to mortality after a breast cancer diagnosis

Abstract: Evidence suggests that certain reproductive factors are more strongly associated with the incidence of lobular than of ductal breast cancer. The mechanisms influencing breast cancer incidence histology may also affect survival. Women with invasive breast cancer (N = 22,302) diagnosed during 1986–2005 were enrolled in a series of population-based studies in three US states. Participants completed telephone interviews regarding reproductive exposures and other breast cancer risk factors. Histologic subtype was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 21 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…Previous studies reported that nulliparity and late age at first childbirth are related to aggressive tumor behavior [37][40]. Our results suggest that high-T class may mediate such effects: nulliparity was associated with the risk of high-T class, particularly in premenopausal ductal carcinomas and late age at first childbirth was associated with high-T class in postmenopausal ductal and lobular carcinomas.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies reported that nulliparity and late age at first childbirth are related to aggressive tumor behavior [37][40]. Our results suggest that high-T class may mediate such effects: nulliparity was associated with the risk of high-T class, particularly in premenopausal ductal carcinomas and late age at first childbirth was associated with high-T class in postmenopausal ductal and lobular carcinomas.…”
Section: Discussionsupporting
confidence: 57%
“…advanced stage, high histological grade, and high proportion of hormone receptor-negative tumors) (5, 19, 24), and consequently poor prognosis (19, 22-24). Multiparity has also been associated with higher mortality, particularly BC-specific mortality (20, 33). Our findings are in line with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies report no association between number of births and prognosis (12-16), other studies report that multiple births are associated with a poorer prognosis (16-19), and still others show improved prognosis among multiparous women (13, 20, 21). These discrepancies may be attributed to different distributions of potential effect measure modifiers such as race and menopausal status, and a different profile of intrinsic subtypes across study populations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a multiplicative interaction was observed between rs2273802 in WARS and age at first live birth on breast cancer risk. Age at first live birth has been established as risk factors for breast cancer owing to different exposure of endogenous hormones . The interaction results may suggest that the effect of rs2273802 may be different between individuals with distinct endogenous hormone levels.…”
Section: Discussionmentioning
confidence: 99%